MODEL MATEMATIKA KETERGANTUNGAN MASYARAKAT TERHADAP MEDIA SOSIAL - Oktavia, Nanda; Rosha, Media (UNIVERSITAS NEGERI PADANG, 2023)
The convenience presented by social media technology leads to dependence on its users. Social media dependence has a bad impact on humans and is very dangerous for its users. Thus it is necessary to analyze how the level of dependence of society on social media. The transmission of social media dependence occurs if there is interaction between communities. The study aims to determine the level of dependence of the community on social media. This research is stated ase basic research and uses literature studies. This research begins with identifying problems, formulating mathematical models, conducting stability analysis at the point and interpreting the mathematical model. Based on the results of the analysis, this point remains free and endemic to people's dependence on social media exists and will be asymptotic stable if it meets some of the conditions of the Routh-Hurwitz criteria. Based on the simulation results, the interaction and the number of people who recover can affect the spread of dependence on social media. The spread of people's dependence on social media will be reduced if the rate of recovery is increased.